2016
DOI: 10.1055/s-0036-1579663
|View full text |Cite
|
Sign up to set email alerts
|

Early and Delayed Effect of Functional Endoscopic Sinus Surgery on Intraocular Pressure

Abstract: Introduction Due to the close anatomical relationship between the paranasal sinuses and the orbit, involvement or injury of the orbit from paranasal sinuses procedures may occur. Objectives We aimed to study the early and delayed effect of endoscopic sinus surgery on intraocular pressure (IOP). Methods We included in the study 38 patients with chronic rhinosinusitis (CRS), undergoing FESS. We performed FESS with the standard anterior to posterior approach. We measured IOP at the same time one day before surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Regarding the relationship between CRS and glaucoma, delayed elevation in IOP was found in patients with CRS who received FESS [15]. Furthermore, in a previous population-based study conducted in Taiwan during a 5-year follow-up interval, CRS of all severities led to the development of OAG with a higher hazard ratio and correlated to the disease interval [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the relationship between CRS and glaucoma, delayed elevation in IOP was found in patients with CRS who received FESS [15]. Furthermore, in a previous population-based study conducted in Taiwan during a 5-year follow-up interval, CRS of all severities led to the development of OAG with a higher hazard ratio and correlated to the disease interval [16].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ocular complications related to the development of CRS, preseptal cellulitis, orbital cellulitis, and subperiosteal abscess have been reported in a cross-sectional study [13]. Changes in intraocular pressure (IOP) in patients with CRS who received FESS has also been demonstrated [14,15], in which significantly elevated IOP was found 6 weeks after the performance of FESS [15]. Additionally, another population-based study showed the development of open-angle glaucoma (OAG) after CRS in Taiwan [16].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic sinus surgery (ESS) represents one of the most performed surgical otorhinolaryngology procedures that require good surgical field visibility. [ 1 ] Haemodynamic optimisation through heart rate (HR) control, during general anaesthesia (GA) for ESS, has been believed to be superior to reduction of systemic vascular resistance and hypotension with respect to the surgical field quality. [ 2 ] Appropriate oral premedication can provide a smooth approach to optimise the intraoperative haemodynamics without compromising patient safety.…”
Section: Introductionmentioning
confidence: 99%